Conscious Delirium of a Traveling Body: The Poetics and Politics of a Creative Practice - Tara Fatehi (Lateral)
The question of political economy in the arts offers a way into a creative-critical reflection on the challenges associated with navigating identity labels and living a freelance artist’s life pressured to conform to institutional expectations particularly within the UK's art scene. This piece is a personal account of a body resisting becoming a symbol, of staying conscious of our socio-political landscape and the ongoing Israeli settler-colonialism. I draw on examples from three of my artworks: the collaborative project From the Lips to the Moon, ongoing nights of longform improvised music and poetry in London; In Observance, a performative research and intervention at the United Nations in Geneva, involving archival documents related to Palestine; and Mishandled Archive, which involves dispersing family photographs and documents in public places, accompanied by daily dances. Through these works, this essay asks: How can historical evidence of imperialism and settler-colonialism be absorbed or resisted within the body? How can we transform loss into movement and togetherness? How late is too late as mounds of rubble and bodies multiply?